Karakteristik Instrumen Literasi Matematika Pada Konten Geometri dan Pengukuran Ditinjau Dari Perspektif Item Response Theory - Nursetyani, Wulan; Susanto, Hari Purnomo; Qudsiyah, Khoirul (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2025)
The research aims to determine the characteristics of mathematical literacy instruments in geometry and measurement content reviewed from the perspective of item response theory. The type of research used is quantitative description. The study subjects were 235 students in grade VIII of junior high school in Pacitan Regency, with details of 108 male students and 127 female students. Item analysis was carried out using IRT. The calculation uses the R program with the help of the mirt package. The study results showed that the mathematics literacy instruments, geometry content, and measurement characteristics were by the 1 PL model. Furthermore, from 8 question items, 7 items were fit and 1 item was not fit. One item that is not fit is item number 7, so the item must be removed. Mathematical literacy instruments in geometry and measurement content consisted of 14.29% of medium category questions and 85.71% of difficult category questions. The instrument is suitable for measuring students who have abilities ranging from -0.78 to 2.85.